2011
DOI: 10.1002/jat.1697
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetyl‐cysteine protects chicken growth plate chondrocytes from T‐2 toxin‐induced oxidative stress

Abstract: T-2 toxin is now considered to be related to bone malformation such as incomplete ossification, absence of bones and fused bones. In this study, primary cultures of chicken tibial growth plate chondrocytes (GPCs) were treated with various concentrations of T-2 toxin (5, 50, and 500 n m) in the absence and presence of N-acetyl-cysteine (NAC) to investigate the effects of the antioxidant NAC on T-2 toxin-induced toxicity. Our results showed that T-2 toxin markedly decreased cell viability, alkaline phosphatase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…This finding suggests that GSH is involved in the cellular defense mechanisms in response to the exposure to this mycotoxin in Caco-2 cells. Similar results were obtained by Tiessen et al (2013) who showed that GSH levels decreased (from 19% to 26%) in a concentration dependent manner in HT29 cells after exposure to 10-50 mM AOH for 1 h. Furthermore, parallel results were observed with mycotoxins from other genera of fungi (Penicillium,Aspergillus and Fusarium), like deoxynivalenol (DON) in human peripheral blood lymphocytes (PBL) (Yang et al, 2014) and Hek-293 (Dinu et al, 2011); Beauvericin (BEA) in Caco-2 cells (Prosperini et al, 2013) and CHO-K1 cells (Mallebrera et al, 2014); Zearalenone (ZEA) in HepG2 cells (Hassen et al, 2007); Ochratoxin (OTA) in LLC-PK1 cells (Schaaf et al, 2002) and T-2 toxin in GPCS cells (He et al, 2011).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This finding suggests that GSH is involved in the cellular defense mechanisms in response to the exposure to this mycotoxin in Caco-2 cells. Similar results were obtained by Tiessen et al (2013) who showed that GSH levels decreased (from 19% to 26%) in a concentration dependent manner in HT29 cells after exposure to 10-50 mM AOH for 1 h. Furthermore, parallel results were observed with mycotoxins from other genera of fungi (Penicillium,Aspergillus and Fusarium), like deoxynivalenol (DON) in human peripheral blood lymphocytes (PBL) (Yang et al, 2014) and Hek-293 (Dinu et al, 2011); Beauvericin (BEA) in Caco-2 cells (Prosperini et al, 2013) and CHO-K1 cells (Mallebrera et al, 2014); Zearalenone (ZEA) in HepG2 cells (Hassen et al, 2007); Ochratoxin (OTA) in LLC-PK1 cells (Schaaf et al, 2002) and T-2 toxin in GPCS cells (He et al, 2011).…”
Section: Discussionsupporting
confidence: 50%
“…Activation of the antioxidative system occurs in order to maintain the intracellular ROS at normal levels and protect from oxidative damage (He et al, 2011). The antioxidant system includes protective mechanisms by glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…However, results published on the effects of T-2 toxin on lipid peroxidation are contradictious. T-2 toxin-induced oxidative stress was found in vitro in chondrocytes (He et al, 2012) and in human cervical cancer cells (Chaudhari et al, 2009a) and in vivo in mice (Chaudhari et al, 2009b), rats (Rizzo et al, 1994;Rocha et al, 2005) and broiler chickens (Mézes et al, 1998;Dvorska et al, 2007) in a dose dependent manner. Most of the previous studies also revealed that T-2 toxin has marked effect on the antioxidant status of animals (Atroshi et al, 2002, Surai, 2002 because of its pro-oxidant properties (Rizzo et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Growth plate cartilage was harvested from the proximal end of the tibia of 6-week-old hybrid broiler chickens and chondrocytes were isolated as previously described [ 35 ]. Briefly, tibial growth plate slices were treated in a digest solution (0.1% type IV collagenase, 0.1% hyaluronidase, 5% FBS) and incubated at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%